The role of women in the fourth gospel - Nortjé, S.J. (1986)
This paper investigates the question whether the Gospel of John treats women any differently from what was customary in ancient Israel and New Testament times. The first section deals with this aspect as comparative material. What follows is a systematic, albeit cursory treatment of the sections of the gospel where women feature in the text. Feminist theology is not a vital part of the discussion but is treated as a phenomenon seeking to secure itself in Scripture passages.
Keywords: Women in New Testament times; Women in ancient Israel; Samaritan Woman; Jesus and women; Feminism; Gospel of John; Theology; Christianity